Edukasi Fisioterapi Untuk Peregangan Ekstremitas Atas pada Pekerja Kontruksi Pembangunan Gedung FIK di UM Metro - Selly Riski Putri; Safun Rahmanto (Pusat Riset dan Inovasi Nasional, 2025)
Muhammadiyah Metro University is one of the universities in Metro Timur District, Metro City, Lampung. Stretching is defined as stretching. Stretching is a form of physical exercise that is done by stretching muscle mass to reach maximum length in order to increase muscle flexibility. The benefits of stretching include increased flexibility, increased range of joint motion, improved circulation, increased muscle elasticity, and relieving stress. Of the 36 workers who participated in the education on March 12, 2025, it was found that construction workers experienced stiffness in the upper extremities. Physiotherapy-based K3 handling can provide preventive efforts against the emergence of physical health problems of employees in the workplace such as muscle pain, joints, and other anatomical disorders caused by microtraumatic. Objective: This program aims to increase knowledge about physiotherapy-based K3 handling for construction workers. Method: This public education involves health promotion regarding physiotherapy education on stretching the upper extremities to construction workers using banner media. The author used a questionnaire to assess the understanding of construction workers. Results: The results of the questionnaire showed an increase in the average score of workers' understanding by 43.75 points, with an average pre-test score of 50 points and an average post-test score of 93.75 points. Conclusion: Public education conducted on construction workers succeeded in increasing workers' understanding of upper extremity stretching physiotherapy education.